A review on the mechanism of high repetition rate pulse interference on the RF front-end of GNSS receivers - Song, Yili; Wang, Huilin; Liu, Wenxiang; Xiao, Wei; Ye, XiaoZhou; Sun, Guangfu (Frontiers in Physics, 2024)
With the rapid advancement of pulse technology, given the extraordinarily high repetition frequency of high-repetition pulse interference, with pulse widths typically ranging from a few nanoseconds to several hundred nanoseconds, it possesses ultra-wideband characteristics, research on how to avoid spectral conflict and malicious interference between these pulse signals and navigation receiver systems has emerged as a pressing and popular issue. This paper introduces the mathematical model of high repetition pulse interference signals. Following this, the paper summarizes and analyses the transient response, nonlinear distortion, and linear distortion that accompany signal processing at the Radio Frequency (RF) front end of the receiver. It concludes that the main source of interference in the limiter’s transient response is peak leakage, the primary factor in low noise amplifier’s (LNA) interference is third-order intermodulation distortion, and filter interference is due to the interlaced response from adjacent pulses. Lastly, the current research progress on the mechanism of high repeti-tion pulse interference with navigation receivers is reviewed, providing reference for future study.